An agent-based model that simulates the spatio-temporal dynamics of sources and transfer mechanisms contributing faecal indicator organisms to streams. Part 1: Background and model description. (15th September 2020) - Neill, Aaron J.; Tetzlaff, Doerthe; Strachan, Norval J.C.; Hough, Rupert L.; Avery, Lisa M.; Kuppel, Sylvain; Maneta, Marco P.; Soulsby, Chris
Abstract: A new M odel for the A gent-based simulation of F aecal I ndicator O rganisms (MAFIO) is developed that attempts to overcome limitations in existing faecal indicator organism (FIO) models arising from coarse spatial discretisations and poorly-constrained hydrological processes. MAFIO is a spatially-distributed, process-based model presently designed to simulate the fate and transport of agents representing FIOs shed by livestock at the sub-field scale in small (<10 km 2 ) agricultural catchments. Specifically, FIO loading, die-off, detachment, surface routing, seepage and channel routing are modelled on a regular spatial grid. Central to MAFIO is that hydrological transfer mechanisms are simulated based on a hydrological environment generated by an external model for which it is possible to robustly determine the accuracy of simulated catchment hydrological functioning. The spatially-distributed, tracer-aided ecohydrological model EcH2 O-iso is highlighted as a possible hydrological environment generator. The present paper provides a rationale for and description of MAFIO, whilst a companion paper applies the model in a small agricultural catchment in Scotland to provide a proof-of-concept. Highlights: Present a new agent-based model for simulating faecal indicator organisms (FIOs). Simulates fate and transport of agents representing a sufficient sample of FIOs. Models loading, die-off, detachment, surface routing, seepage and channel routing. Hydrological environment is generated by a robustly-constrained hydrological model. Present EcH2 O-iso as an appropriate hydrological environment generator.